Розвиток досліджень з історії науки через аматорські розвідки на початку 20 ст.: доробок астронома Миколи Барабашова - Гутник, Марина Валеріївна (ФОП Жукова Ірина Віталіївна, 2024)
Розглядається процес впровадження науково-технічних технологій, ідей та методів західноєвропейської науки і техніки у різні сфери суспільного життя мешканців Російської імперії, частиною якої на той час була Україна. Наголошується на значному відставанні проти досліджень у країнах Західної Європи та Америки. В той час, коли на Заході вже існували спеціальні кафедри з історії науки й техніки, в Російській імперії ця галузь науки була ще на ранніх стадіях формування, а значну частину наукових досліджень ініціювали окремі вчені, часто на власному ентузіазмі. Аналіз робіт тогочасних дослідників показав, що розвиток науки і техніки відбувався одночасно в різних країнах, але в Російській імперії цей процес часто був ініційований не централізовано, а на рівні окремих наукових осередків, зокрема, університетів, які стали центрами концентрації наукової думки в першій половині 19 ст. Характерною особливістю перших наукових товариств в Російській імперії була їх енциклопедичність і відсутність вузької спеціалізації. Наприклад, Вільне економічне товариство в Петербурзі та Філотехнічне товариство в Харкові включали в себе дослідників з різних галузей науки. Лише в другій половині 19 ст. починається процес спеціалізації наукових організацій та диференціації наукових дисциплін, що сприяло подальшому розвитку науки й техніки в Російській імперії. Зазначається, що окрім офіційних наукових установ, значний внесок у розвиток науки внесли аматорські дослідження. В цей час виникли наукові товариства, які об’єднували як професіоналів, так і серйозних аматорів, що намагалися задовольнити своє прагнення до наукової діяльності. Роль аматорських досліджень у розвитку науки особливо підкреслюють сучасні дослідники. Україна також має свої приклади успішних аматорів-науковців. Яскравим прикладом є Микола Павлович Барабашов, який на початку 20 ст. починав як аматор, але згодом став провідним астрономом. Його діяльність, як і діяльність інших аматорів, не лише сприяла розвитку науки, але й формувала наукову спільноту, яка мала великий вплив на подальший розвиток досліджень в Україні. Аматорські дослідження відігравали важливу роль у формуванні «великої» науки, оскільки багато наукових установ і досліджень виросли саме з ініціатив аматорів, які, незважаючи на відсутність професійної підготовки, часто робили важливі наукові відкриття. Це явище заслуговує на увагу в контексті історії науки й техніки, адже воно показує, як навіть у несприятливих умовах можна було досягати значних наукових успіхів.

The process of introducing scientific and technical technologies, ideas, and methods of Western European science and technology into various spheres of public life in the Russian Empire, of which Ukraine was a part at the time, is being considered. Emphasis is placed on the significant lag in research compared to Western Europe and America. While the West already had specialized departments in the history of science and technology, in the Russian Empire, this field of science was still in the early stages of formation, and much of the scientific research was initiated by individual scientists, often driven by their own enthusiasm. An analysis of the works of researchers of that time showed that the development of science and technology was happening simultaneously in different countries, but in the Russian Empire, this process was often initiated not centrally, but at the level of individual scientific centers, particularly universities, which became centers of concentrated scientific thought in the first half of the 19th century. A characteristic feature of the first scientific societies in the Russian Empire was their encyclopedic nature and lack of narrow specialization. For example, the Free Economic Society in St. Petersburg and the Philotechnical Society in Kharkiv included researchers from various fields of science. It was only in the second half of the 19th century that the process of specialization of scientific organizations and differentiation of scientific disciplines began, which contributed to the further development of science and technology in the Russian Empire. It is noted that, in addition to official scientific institutions, amateur research also made a significant contribution to the development of science. During this time, scientific societies emerged that brought together both professionals and serious amateurs who sought to satisfy their desire for scientific activity. The role of amateur research in the development of science is particularly emphasized by modern researchers. Ukraine also has its own examples of successful amateur scientists. A striking example is Mykola Pavlovych Barabashov, who began as an amateur at the beginning of the 20th century but later became a leading astronomer. His activities, like those of other amateurs, not only contributed to the development of science but also formed a scientific community that had a significant impact on the further development of research in Ukraine. Amateur research played an important role in the formation of “major” science, as many scientific institutions and studies grew out of amateur initiatives, and despite the lack of professional training, amateurs often made important scientific discoveries. This phenomenon deserves attention in the context of the history of science and technology, as it demonstrates how significant scientific achievements could be made even under unfavorable conditions.
The development of research in the history of science through amateur investigations at the beginning of the 20th century: the contribution of astronomer Mykola Barabashov
Keywords: історія науки; М. П. Барабашов; аматорські дослідження; Харків; Харківський університет; краєзнавство; біографістика; персоналії; ректор; history of science; M. P. Barabashov; amateur research; Kharkiv; Kharkiv University; local history; biography; personalities; rector